A hemodynamic model to guide blood pressure control during deliberate hypotension with sodium nitroprusside in children - Barrett, Jeffrey S.; Hirankarn, Sarapee; Holford, Nick; Hammer, Gregory B.; Drover, David R.; Cohane, Carol A.; Anderson, Brian; Dombrowsky, Erin; Reece, Tammy; Zajicek, Anne; Schulman, Scott (Frontiers in Pharmacology, 2015)
Sodium nitroprusside (SNP) has been widely used to control blood pressure in infants and children. The goals of this analysis were to develop models that describe the hemodynamic response to SNP dosing in pediatric patients; examine sources of variation in dose-response, defining age and size dependencies; and determine vulnerable populations or patient subtypes that may elicit dosing modifications. A multi-center, randomized, double-blinded, parallel-group, dose-ranging, effect-controlled study, followed by an open-label dose titration of an intravenous infusion of SNP was undertaken in 203 pediatric subjects, who required deliberate hypotension or controlled normotension during anesthesia. A total of 3,464 MAP measurements collected from 202 patients during the study’s blinded phase, including baseline measurements up to 6 min prior to the blinded were available for analysis. A population K-PD model was developed with a one-compartment model assumed for SNP. Size differences in CL and V of the effect compartment were described using theory-based allometry. An inhibitory sigmoidal Emax model was used to describe the effect of SNP. A power function of age was used to describe age-related differences in baseline MAP. A mixture model of two groups with low and high EC50 was used to explain variability in MAP response. Change in MAP was characterized by a linear disease progression slope during the blinded phase. In the final population model, CL and V increased with weight, and baseline MAP increased with age. The effect compartment half-life of SNP was 13.4 min. The infusion rate producing 50% of Emax (ER50) at steady state for high EC50, was 0.34 µg/kg/min and for low EC50 0.103 µg/kg/min. The K-PD model well describes initial dosing of SNP under controlled circumstances; model-based dosing guidance agrees with current practice. An initial titration strategy supported via algorithm-based feedback should improve maintenance of target MAP.